Analisis Kelayakan Investasi Mesin Las Listrik Weldteco NBC – 250f Guna Meningkatkan Produktivitas - Cahya Syahyanda, Aulia Isha; Muhimatul Khoiroh, Siti (SURYA TEKNIKA, 2024)
CV. Karya Cipta Baru is one of the companies operating in the remanufacturing industry for heavy-duty vehicles such as trucks, trailers, and others. The company is planning to invest in electric welding machines to expedite the process of repairing truck trailers. Feasibility analysis and productivity analysis will be conducted to determine the viability of this investment. Sensitivity analysis is performed using the NPV calculation method, resulting in an NPV of Rp. 157,491,591. The calculation of PP estimates a payback period of 4 months and 18 days. The IRR calculation yields an investment return rate of 234%. And the PI calculation shows a profitability index of 8.16. Productivity analysis is also conducted using the Marvin E. Mundel method to assess the impact of the investment in electric welding machines. From the productivity analysis results, the investment is deemed feasible as it can increase the company's sales and net profit